Remotely Sensed Deformation and Thermal Anomalies at Mount Pagan, Mariana Islands - Henderson, Scott T.; Pritchard, Matthew E.; Cooper, Jennifer R.; Aoki, Yosuke (Frontiers in Earth Science, 2019)
Volcanic islands in remote settings are challenging to study with ground-based instrumentation; nevertheless it is important to define “normal” background activity at these volcanoes because they pose threats to air and sea traffic. A combination of remote sensing methods is critical to adequately characterize volcanic activity, and in this study we present space-based observations of both thermal anomalies and surface deformation at Pagan Island in the Mariana Island Arc. Mt. Pagan produced a large eruption (>0.1 km3) in 1981, and recent smaller eruptions (>0.001 km3) in 2011 and 2012 that triggered volcanic ash advisories. In this study we examine available Interferometric Synthetic Aperture Radar (InSAR) from Envisat and ALOS between October 2004 and June 2010 for precursory deformation leading up to the most recent eruptions. Although we do not observe evidence for shallow magma reservoir inflation, we do observe a zone of subsidence of up to -3 cm/yr located on the northern flank likely caused by continuing scoria compaction of 1981 eruptive deposits. CosmoSkyMed InSAR measurements spanning the October 2012 eruption also shows deposit subsidence, but no detectable co-eruptive deflation. We also present remotely-sensed thermal time series from the MODIS and ASTER instruments spanning over a decade. There are two distinct locations of anomalous surface temperatures on the island, which correlate with previously documented, fumarolically active vents at South Pagan and Mt. Pagan. Ultimately, we did not find thermal or deformation precursors for recent eruptive activity, plausibly because the volcano had an open conduit and persistent degassing during this time period. We compare and contrast the efficacy of various sensor types currently available to characterize transient dynamics at small and remote volcanic islands such as Pagan.